Zoledronate alters natural progression of tissue‐engineered vascular grafts. Issue 10 (2nd September 2021) - Chang, Yu‐Chun; Li, Junlang; Mirhaidari, Gabriel; Zbinden, Jacob; Barker, Jenny; Blum, Kevin; Reinhardt, James; Best, Cameron; Kelly, John; Shoji, Toshihiro; Yi, Tai; Breuer, Christopher
Abstract: Macrophages are a critical driver of neovessel formation in tissue‐engineered vascular grafts (TEVGs), but also contribute to graft stenosis, a leading clinical trial complication. Macrophage depletion via liposomal delivery of clodronate, a first‐generation bisphosphonate, mitigates stenosis, but simultaneously leads to a complete lack of tissue development in TEVGs. This result and the associated difficulty of utilizing liposomal delivery means that clodronate may not be an ideal means of preventing graft stenosis. Newer generation bisphosphonates, such as zoledronate, may have differential effects on graft development with more facile drug delivery. We sought to examine the effect of zoledronate on TEVG neotissue formation and its potential application for mitigating TEVG stenosis. Thus, mice implanted with TEVGs received zoledronate or no treatment and were monitored by serial ultrasound for graft dilation and stenosis. After two weeks, TEVGs were explanted for histological examination. The overall graft area and remaining graft material (polyglycolic‐acid) were higher in the zoledronate treatment group. These effects were associated with a corresponding decrease in macrophage infiltration. In addition, zoledronate affected the deposition of collagen in TEVGs, specifically, total and mature collagen. These differences may be, in part, explained by a depletion of leukocytes within the bone marrow that subsequently led to a decrease in the number of tissue‐infiltrating macrophages. TEVGs from zoledronate‐treated mice demonstrated a significantly greater degree of smooth muscle cell presence. There was no statistical difference in graft patency between treatment and control groups. While zoledronate led to a decrease in the number of macrophages in the TEVGs, the severity of stenosis appears to have increased significantly. Zoledronate treatment demonstrates that the process of smooth muscle cell‐mediated neointimal hyperplasia may occur separately from a macrophage‐mediated mechanism.